'Join us on our journey': exploring the experiences of children and young people with type 1 diabetes and their parents. (January 2014) - Kime, Nicky
Abstract: This paper focuses on children and young people with type 1 diabetes and on their parents, and their experiences of diabetes care provision. Nine acute hospitals in the Yorkshire and the Humber region, UK, were recruited to participate in a qualitative research study. Children and young people with type 1 diabetes, aged 6–25, and their parents (approximately 250 participants), took part in talking groups to find out about their experiences of diabetes care provision. Findings show that there are key areas for improvement in the future diabetes care provision for children and young people, including communication and support, schools, structured education and transition. These have important implications for practice and service redesign. This study is thought to be the first of its kind to consult with children, young people and parents to find out about their experiences of type 1 diabetes care provision. The research findings add to the current evidence base by highlighting the disparities in care, the urgent need for change in the way services are delivered and the involvement of service users in this process. Copyright © 2014 John Wiley & Sons.